Trastuzumab monotherapy as maintenance treatment for metastatic HER2+ vulvar Paget disease: systematic review and case report - Dalila Incognito; Massimiliano Berretta; Giosuè Giordano Incognito; Ferdinando Antonio Gulino; Roberta Foti; Vincenzo Canzonieri; Claudia Gelsomino; Marco Palumbo; Antonio Picone (Gynecologic Oncology Reports)
Vulvar Paget’s disease (VPD) is a rare intraepithelial malignancy frequently associated with HER2 overexpression. This study offers insights into managing HER2-positive extramammary Paget’s disease cases in which trastuzumab monotherapy was administered as manteinance therapy. We report the case of a 52-year-old woman with VDP and lymph node involvement, who was initially treated with paclitaxel and trastuzumab, for which chemotherapy was discontinued due to significant side effects, and trastuzumab as maintenance therapy was continued, resulting in significant regression of metastatic lesions. Additionally, a systematic review was conducted. The review included 6 studies from 2008 to 2020. Complete response was achieved in 2 out of 7 (28.6%) cases, partial response in 4 (42.9%) cases, and stable disease in 1 (14.3%) case. Mild moderate headache and flushing during trastuzumab manteinance therapy were reported in only one patient. In conclusion, trastuzumab monotherapy may be a valid alternative option, particularly in patients unable to tolerate combination chemotherapy. These findings emphasize the importance of personalized treatment approaches.